ANALISIS IMPLEMENTASI HUKUMAN MATI DALAM HUKUM PIDANA ISLAM PRESPEKTIF KEADILAN DAN HAK ASASI MANUSIA - Alifa Dhiya Rahadi; Alya Devitri (ADISAM PUBLISHER, 2024)
The purpose of ths study is to investgate the impact of the implementation of Law No. 2023 on the Crimnal Code which regulates the dath penaly in Indonesia. This law aims to change the deah penalty frm a basic legal provision to a special law based on Islamic law and positive law. By using socio-legal methodology, this research focuss on to main aspect: the reconstruction of deah penlty regulation in Indonsia and the role of Islamic Law in strengthening the reconstruction. The resuls of ths study lead to two main conclusions: ndonesia seeks to limit its use. People sentenced to death are given the opportunity to improve their behavior within a (10 years). If the convict shows good behavior during that period. This policy is considered as a last resort in situations that are difficult to reverse, as well as an attempt to balance in Indonesia. In addition, Islamic values as a source of law also strengthen the pro and con arguments, given that the death penalty in the Islamic view is still recognized as part of the legitimate practice of punishment